Algal study in the springs and streams from Shaqlawa district, Erbil Province, Iraq II- Zygnematales - Toma, Janan Jabbar; Aziz, Farhad Hassan (Iraqi Journal of Science, 2022)
Zygnematales an order of green algae in Shaqlawa District Erbil, Kurdistan Region, Iraq, has been studied in eighteen sites, distributed between twelve springs and six along the streams within Shaqlawa district from September2019 to August2020. A total of 116 species belonging to 9 genera were identified. The most dominant genera included Spirogyra and Cosmarium (31, 30) taxa respectively. Out of them, 30 species were recorded for the first time in Iraq. Newly found genera included one species each for Cylindrocystis, Debarya, Hallasia and Staurastrum, nine species belonged to Mougeotia, three species returned to Closterium, and fourteen genera were related to Cosmarium .Growth of Zygnemataceae and Desmids increased in the summer than during the winter season. A brief description as well as the measurement is given for each species.